Computer aided facilities management in the tender processing [electronic resource] - 321264 Azmi Ali (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Pengurusan Fasiliti)) - Universiti Teknologi Malaysia, 2006